Composition and Health Effect of Tea Plant (Camellia sinensis) - Elmas, Cemre; Gezer, Ceren (Sidas Medya A.S., 2019)
Tea is one of the most widely consumed beverages worldwide. The effect of tea on human health is often related to phytochemicals in its composition. During tea production, fermentation may produce variations by the amount and type of bioactive components present in the tea content. Catechins in the tea polyphenols show antioxidant activity. These components contribute to the prevention of diseases such as obesity, diabetes, cardiovascular diseases and cancer. It is also stated that these components may have protective effects against viral, bacterial and neurological diseases. In this study, it is aimed to review the bioactive constituents of tea and their effect on human health. © 2019 Authors. All rights reserved.
Çay Bitkisinin (Camellia sinensis) Bileşimi ve Sağlık Etkileri
Keywords: Camellia sinensis; Epigalloatechin gallate; Flavonoid; Tea